Faktor-Faktor Tingkat Kepuasan Tenaga Kerja terhadap Produktivitas Sales Promotion Girl (SPG) pada PT. Garuda Inovasi Semesta (Komplit) Bandar Lampung - Sutadipraja, Edwin; Asmuni, Idris (Universitas Mitra Indonesia, 2022)
This study aims to obtain empirical evidence on the influence of salaries, incentives and education on performance productivity.